Rekonstruksi Epistemologi Pendidikan Islam: Sintesis Normatif, Historis, Dan Filosofis Menuju Model Berkelanjutan - Widia Yelsa; Fatmawati; Ahmad Lahmi (STKIP Subang, 2025)
Islamic education is a dynamic discipline that stands on three main pillars: normative, historical and philosophical sources. This article aims to analyze the characteristics of these three sources and how they are integrated to form a holistic Islamic education system. Through the library research method, it is found that normative sources (the Qur'an and Hadith) provide the foundation of absolute values, historical sources provide the empirical context and institutional evolution, while philosophical sources offer a framework for critical thinking about the nature of man and science. The study results show that the dichotomy between normative and historical aspects can be bridged through integrative-interconnective epistemology. The conclusion of this study emphasizes that the contemporary Islamic education curriculum must be able to dialogue the eternal revelation with the changing reality of the times in order to remain relevant and progressive.